Comparison of Transvaginal Ultrasound Cervical Length with Bishop Score in Predicting Cesarean Section after Labor Induction: Ultrasound Cervical Length Versus Bishop Score After Labor Induction - Pirzada, Hina; Shabbier, Nosheena; Ara, Iffat; Hussain, Samar; Akram, Rabia; Khokhar, Shabana (Pakistan Journal of Health Sciences, 2024)
A critical aspect of obstetric care aimed at initiating or augmenting childbirth when natural processes are deemed insufficient or unsafe, employing various methods to ensure maternal and fetal well-being Objective: To compare the transvaginal ultrasound cervical length with bishop score in predicting cesarean section after labor induction. Methods: A comparative cross-sectional study was conducted at the Department of Gynecology and Obstetrics Azad Jammu Kashmir Medical College (AJKMC), Muzaffarabad from January 2023 to June 2023. A total of 110 pregnant women aged 18 to 35 years having gestational age ≤ 40 weeks were included who underwent transvaginal ultrasound (TVS) for measuring cervical length (CL) measurement and Bishop Score assessment before labor induction. Primary outcomes included cesarean section rates post-induction, with secondary outcomes covering maternal and neonatal variables. Results: The study involved 110 participants, with a mean age of 25.9 ± 4.00 years. Mean Bishop Score was 4.53 ± 2.06, and the mean cervical length measured by transvaginal ultrasound was 26.6 ± 7.37 mm. Misoprostol was the primary induction method (65.5%), with an overall Cesarean Section rate of 35.5%. Comparing CS and VD groups, BS was lower in CS (3.74 ± 2.20 vs. 4.96 ± 1.86, p = 0.005), while CL was higher (31.1 ± 6.70 mm vs. 24.1 ± 6.53 mm, p < 0.001). Conclusion: Our study found that transvaginal ultrasound (TVUS) measurement of cervical length (CL) >27 mm demonstrated superior predictive ability for cesarean section (CS) following labor induction compared to the Bishop Score (BS) ≤5.